Competition Between Regions With Respect to Industrial Support - A Theoretical Model - John Dewhurst (European Regional Science Association (ERSA), 2006)
In recent years it seems that both regions and cities appear to have become more eager to present themselves as regions or cities in which new or mobile firms in certain industrial sectors (especially perhaps biotechnology) should locate. At the same time, in the UK at least, there has been devolution of the administration of regional policy, albeit with specific targets being set by the national government. Thus cities and regions have become, at least in part, more able to combine their publicity with financial support for the particular industrial sector they wish to foster. In this paper a model is developed which has the following properties. Cities allocate monies between two types of expenditure, (i) support for a nascent industry and (ii) support for social policies, with payoffs that differ for different cities. It is shown that, if firms in the nascent industry are attracted by relatively high levels of support, cities will generally spend more on industrial support than the national government would. This simple model is similar to those developed in the literature on Tax Competition. This feature allows a commentary to be made on both the policy implications and possible extensions of the model.
Keywords: 330